Relative health-related quality of life after treatment of unruptured intracranial aneurysms: long-term outcomes and influencing factors. (March 2019) - Dammann, Philipp; Wittek, Paula; Darkwah Oppong, Marvin; Hütter, Bernd-Otto; Jabbarli, Ramazan; Wrede, Karsten; Wanke, Isabel; Mönninghoff, Christoph; Kaier, Klaus; Frank, Benedikt; Müller, Oliver; Kleinschnitz, Christoph; et al.
Health-related quality of life (HRQOL) is an important clinical outcome parameter. Its analysis is particularly meaningful to patients with minor functional impairment. The main goal of this study was to assess long-term data of HRQOL and their variables for patients undergoing treatment for unruptured intracranial aneurysms (UIAs). Therefore, a cross-sectional study of HRQOL (SF-36 questionnaire) was conducted in patients treated for UIA using a telephone survey assessing numerous medical and sociodemographic variables. A total of 96 patients with a follow up longer than 36 months post-treatment were included. HRQOL results were compared with the German reference population. Uni- and multivariate analyses were performed to detect variables with an impact on outcome. After a mean follow up of 57.75 ± 13.56 months, patients with treated UIAs showed a significant decrease in the mental health domains 'role emotional' and 'social functioning' and the 'mental health component score' (MHCS) compared with the age- and sex-matched reference population. Overall, 47% of the patients showed a clinically and psychosocially relevant decrease compared with the mean MHCS of the reference population. Multivariate analysis suggests that mainly the treatment modality (coiling versus clipping) and additional remaining untreated UIAs negatively impacted mental HRQOL. In conclusion, the partly significant losses in HRQOL identify the necessity for less-wearing treatment strategies and a better prediction of risk of UIA rupture. Our results indicate that certain factors in the guidance and management of patients undergoing endovascular treatment may negatively affect their mental HRQOL. The relevance of additional UIAs remaining untreated on HRQOL is a new finding that should be considered in the counseling of patients with multiple UIAs.